Kojenecka umrtnost ve smecenske farnosti v letech 1730-1779 (na zaklade matrik) - Prazakova, J (Demografie, 1984)
Infant mortality in the parish of Smecno, Czechoslovakia, is analyzed for the period 1730-1799 using data from parish registers. Variations in infant mortality over time and by sex are noted. (summary in ENG, RUS)
Keywords: Československo; populační charakteristiky; Demographic Factors; východní Evropa; Demography; mortalita; Eastern Europe; Population Characteristics; Social Sciences; populace; registrace; demografie; Mortality; Registries; Europe, Eastern; Infant Mortality; časové faktory; Europe; Parish Registers; sexuální faktory; Czechoslovakia; sociální vědy; Population; Developed Countries; Evropa; Historical Demography; Sex Factors; Differential Mortality; Historical Survey; populační dynamika; Population Dynamics; kojenecká mortalita; vyspělé země; Time Factors